Digital slow : Brahmanisms, Zetetic Wild Sciences and Pedagogics - Reinertsen, Anne B. (Critical Studies in Teaching and Learning, 2023)
Our digital society and education systems are produced and simultaneously constrained within powerful political discourses. Brahmanisation (Piketty, 2019) of left-wing parties and policies is an example of this preventing substantial and conflictual but productive transformation, hence leaving the educational field in stasis. This article is a critique of discursive productions of policies and offers a view of digitalisation and/or education collectively produced through zetetic or curious wild science, productive doubts and Slow scholarships, ultimately turning inquiry into our systems’ signature pedagogics and/as change: inquiry as pedagogy as change. The focus is the becoming-child infused with immanent life, our educational institutions and policies turned into spaces for exploring and experimenting with new ways of minded mattered living, and making possible the realisation of post-structural and more-than-human concepts such as the disintegration of subjectivity. All concepts are seen as critical, hence simultaneously performative and methodological, as critical engagements oriented towards inclusion, sensed democracy.